2022
DOI: 10.3389/fpsyg.2022.837752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Media Usage on Consumers’ Purchase Intention in Social Commerce: A Cross-Cultural Empirical Analysis

Abstract: Social commerce has produced enormous economic benefits as well as challenges for organizations, individuals, and industries. However, social media usage does not necessarily generate users’ intention to purchase on social commerce websites. How social media usage influences users’ purchase intention on social commerce websites still deserves more scholarly attention and this seems particularly important when social commerce transcends borders and countries. Taking an interdisciplinary perspective, the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 126 publications
(193 reference statements)
0
14
0
2
Order By: Relevance
“…Another study found that social media usage, social influence, drive for environmental responsibility, and perceived trust in social media are major antecedents of consumers' sustainable purchasing attitudes [46]. The sample should ideally represent a diverse range of individuals who engage with social media and have an interest in fitness services.…”
Section: Social Media Influence and Purchasing Intentions For Sustain...mentioning
confidence: 99%
“…Another study found that social media usage, social influence, drive for environmental responsibility, and perceived trust in social media are major antecedents of consumers' sustainable purchasing attitudes [46]. The sample should ideally represent a diverse range of individuals who engage with social media and have an interest in fitness services.…”
Section: Social Media Influence and Purchasing Intentions For Sustain...mentioning
confidence: 99%
“…While some studies have explored the impact of social media platforms on users' purchase intentions, others have investigated the impact of social connections on consumer behavior. For example, Hu and Zhu (2022) studied the impact of social media platform usage on users' purchase intentions, while Mikalef et al (2017) investigated how the characteristics of social commerce platforms affect users' purchase intention and participation in word-of-mouth communication. On the other hand, social media commerce involves not only buyers or sellers but also individuals with social connections on the platform, which affects the influence of information on social media.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusively, purchasing behaviour through a strong preference for products or service in Malaysia among Indonesian students through s-commerce compared to their own country has brought an enormous economic benefit to Malaysia's s-commerce economy. In addition, there are a lot of s-commerce benefits, such as being able to bring new business opportunities, optimal advertising and promotion, generate an excellent platform to share intelligent shopping experiences, and emphasis on enjoyment of people-oriented purchasing experiences (Hu & Zhu, 2022;). However, s-commerce is still in its infancy in Malaysia, nevertheless, and there needs to be more research on the critical elements influencing the purchase behaviour of s-commerce users, particularly Indonesian students studying there (Hu & Zhu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are a lot of s-commerce benefits, such as being able to bring new business opportunities, optimal advertising and promotion, generate an excellent platform to share intelligent shopping experiences, and emphasis on enjoyment of people-oriented purchasing experiences (Hu & Zhu, 2022;). However, s-commerce is still in its infancy in Malaysia, nevertheless, and there needs to be more research on the critical elements influencing the purchase behaviour of s-commerce users, particularly Indonesian students studying there (Hu & Zhu, 2022). Regretfully, should Malaysia fail to seize the chances presented by contemporary s-commerce technology, it will be more susceptible to economic upheavals and, consequently, fall behind other industrialised nations with more sophisticated technological infrastructure when it comes to international competition.…”
Section: Introductionmentioning
confidence: 99%